Serological Evidence of Exposure to Spotted Fever Group and Typhus Group Rickettsiae in Australian Wildlife Rehabilitators - Karen O. Mathews; David Phalen; Jacqueline M. Norris; John Stenos; Jenny-Ann Toribio; Nicholas Wood; Stephen Graves; Paul A. Sheehy; Chelsea Nguyen; Katrina L. Bosward (Pathogens, 2021)
Rickettsioses are arthropod-borne zoonotic diseases, several of which occur in Australia. This study aimed to assess the exposure levels and risk factors for Rickettsia spp. among Australian wildlife rehabilitators (AWRs) using serology, PCR and a questionnaire. Antibody titres against Spotted Fever Group (SFG), Typhus Group (TG) and Scrub Typhus Group (STG) antigens were determined using an immunofluorescence assay. PCR targeting the gltA gene was performed on DNA extracts from whole blood and serum. Logistic regression was used to identify risk factors associated with seropositivity. Of the 27 (22.1%; 27/122) seropositive participants all were seropositive for SFG, with 5/27 (4.1%) also positive for TG. Of the 27 positive sera, 14.8% (4/27) were further classified as exposure to R. australis, 3.7% (1/27) to R. honei, 3.7% (1/27) to R. felis and 77.8% (21/27) were classified as ‘indeterminate’—most of which (85.7%; 18/21) were indeterminate R. australis/R. honei exposures. Rickettsia DNA was not detected in whole blood or serum. Rehabilitators were more likely to be seropositive if more than one household member rehabilitated wildlife, were older than 50 years or had occupational animal contact. These findings suggest that AWRs are at increased risk of contracting Rickettsia-related illnesses, however the source of the increased seropositivity remains unclear.